A Novel P1B-type Mn2+-transporting ATPase is required for secreted protein Metallation in mycobacteria - Padilla Benavides, Teresita (2013)
Transition metals are central for bacterial virulence and host defense. P1B-ATPases are responsible for cytoplasmic metal efflux, and play roles either in limiting cytosolic metal concentrations or in the maturation of secreted metalloproteins. The P1B-ATPase, CtpC, is required for Mycobacterium tuberculosis survival in a mouse model (Sassetti and Rubin (2003) Proc. Nat. Acad. Sci. 100, 12989-12994). CtpC prevents Zn2+ toxicity, suggesting a role in Zn2+ export from the cytosol (Botella, et al., (2011) Cell Host Microbe 10, 248-259). However, key metal coordinating residues and overall structure of CtpC are distinct from Zn2+-ATPases. We found that isolated CtpC has metal dependent ATPase activity with a strong preference for Mn2+ over Zn2+ . In vivo, CtpC is unable to complement Escherichia coli lacking a functional Zn2+-ATPase. Deletion of M. tuberculosis or M. smegmatis ctpC leads to cytosolic Mn2+ accumulation but no alterations in other metals levels. While ctpC-deficient M. tuberculosis is sensitive to extracellular Zn2+ , the M. smegmatis mutant is not. Both ctpC mutants are sensitive to oxidative stress, which might explain the Zn2+-sensitive phenotype of the M. tuberculosis ctpC mutant. CtpC is a high affinity/slow turnover ATPase, suggesting a role in protein metallation. Consistent with this hypothesis, mutation of CtpC leads to a decrease of Mn2+-bound to secreted proteins and of the activity of secreted Fe/Mnsuperoxide dismutase, particularly in M. smegmatis. Alterations in the assembly of metalloenzymes involved in redox stress response might explain the sensitivity of M. tuberculosis ctpC mutants to oxidative stress, grow and persistence defects in mice infection models.